The Adobe Photoshop CS3 book for digital photographers - Kelby, Scott (Indianapolis, Indiana : New Riders, 2008)
A step-by-step handbook takes readers through the fundamental principles and techniques of the digital photography editing process using Adobe Photoshop CS3, covering everything from color correction and digital body-sculpting to organization and output
Includes bibliographical references (p. 459) and index
Keywords: Adobe Photoshop; Adobe Photoshop (Computer software); Photography -- Digital techniques; Computer graphics -- Computer programs; Computer graphics